Classification of functional recovery of anterior cruciate ligament copers, non-copers, and adapters. Issue 10 (18th August 2006) - Button, K; van Deursen, R; Price, P
Abstract : Objectives: ( a ) To identify whether differences exist in the pattern of recovery with respect to functional outcomes for acutely ruptured anterior cruciate ligament deficient (ACLD) copers, adapters, and non-copers. ( b ) To identify clinically relevant outcomes that could distinguish between three functional subgroups. Methods: A longitudinal study was used to measure gait variables and distance hop at regular intervals after injury using a digital camcorder and computer for quantitative analysis. A sample of 63 ACLD subjects entered the study; 42 subjects were measured at least three times. At 12–36 months after injury, subjects were classified as functional copers, adapters, or non-copers on the basis of which of their preinjury activities they had resumed. To determine the pattern of recovery, repeated measurements were analysed using a least squares fit of the data. Results: 17% of ACLD subjects were classified as functional copers, 45% as adapters, and 38% as non-copers. Only 5% of those who participated in high demand activities before injury returned to them. ACLD copers had recovered above the control mean for all gait variables by 40 days after the injury. Hopping distance did not recover to the control mean. Non-copers struggled to recover to control limits and remained borderline for all the gait variables. Conclusions: Distinctive patterns of functional recovery for three subgroups of ACLD subjects have been identified. Gait variables and activity level before injury were the most useful variables for distinguishing between the subgroups. If potential for recovery is identified early after injury, then appropriate treatment can be given.